O projeto escola ecológica em rede : o olhar de alunos/as do ensino fundamental da rede pública municipal de Uberaba-MG - Costa, Emylia Angélica da (2014)
While educational practice, Environmental Education integrates a set of social relations that emerged around the concern with the environment called environmental field. In schools, activities aimed at EA, have shown significant growth, and projects are the most frequently reported among the methodological possibilities for the realization this space. This research follows a qualitative exploratory perspective and has as its object of study the relationship between the Ecological School Network, a project developed by the Cultural Department of the Municipal Secretariat of Education and Culture of Uberaba / MG, and students participating in this project. The main objective of this study is to know the Ecological School Network Project from the speech of its participants. Documentary analysis, focus groups with students and interviews with the coordinators of the project in schools to understand and discuss this relationship, the following data collection instruments were used. Data were collected between February and July 2013 in three local elementary schools Uberaba. Photos belonging to the Project were used during the focus groups, as enhancer elements for the subjects to express their opinions. The first contact with the photographs, prints and slogans were submitted. The first picture, the most striking image was chosen among the participants. It was found that the choices do not restrict yourself to only those belonging to their respective schools, but their looks were also aimed at the photos of other schools. It was understood that students have a very fragmented view of representations of the environment. However, it is noteworthy that even categorizing the photographs based on a classification of the environment, as established by several authors is difficult to group words and images in just a conception, however, the naturalistic conception was prevalent in the choice of the photographs and the speeches of the students. The selected images and their stories showed the choices within the various participating schools, in relation to the conduct of activities proposed by the Ecological School Project Network. Group work, the implementation of vegetable and flower gardens in schools and the activity of storytelling were issues raised by students in their speech since appeared in several photographs from the collection of design in different schools.